2015
DOI: 10.1021/acsami.5b00633
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Method To Assemble Nanostructured Ag@ZnO on Cotton Fabrics: Application as Self-Cleaning Flexible Materials with Visible-Light Photocatalysis and Antibacterial Activities

Abstract: A bioinspired mineralization route to prepare self-cleaning cotton fabrics by functionalizing their surface with nanostructured Ag@ZnO is demonstrated herein. In a polyamine-mediated mineralization process, while the nucleation, organization and coating of ZnO is done directly from water-soluble zinc salts under mild conditions, the entrapped polyamine in the ZnO matrix acts as reducing agent to generate Ag(0) from Ag(I) at room temperature. The Ag@ZnO coated cotton fabrics are characterized by FESEM, HRTEM, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 36 publications
0
61
0
Order By: Relevance
“…The Ag-embedded samples showed higher absorption intensities in the visible region. This was attributed to the surface plasmon absorption characteristics of Ag [14,23,27,33,45,53]. The absorption edges (or the band gap) were determined from plots of [αhν] 1/2 versus hν.…”
Section: Uv-visible Absorption Raman Spectra and Optical Propertiesmentioning
confidence: 99%
“…The Ag-embedded samples showed higher absorption intensities in the visible region. This was attributed to the surface plasmon absorption characteristics of Ag [14,23,27,33,45,53]. The absorption edges (or the band gap) were determined from plots of [αhν] 1/2 versus hν.…”
Section: Uv-visible Absorption Raman Spectra and Optical Propertiesmentioning
confidence: 99%
“…The key points of photoinduced antibacterial behavior are: 1) green and environmental protection; 2) easy manufacturing process, which is convenient for mass production and application in the future; 3) low toxicity or innocuous for normal tissues; 4) enhance photoinduced capacity, which can expand absorption area to realize full‐spectrum solar‐energy driving and used heterogeneous structure to achieve charge carrier promoting separation …”
Section: Antimicrobialmentioning
confidence: 99%
“…Self-cleaning materials are attracting more and more attention for its convenience and environment friendliness [145,146,147,148,149,150,151,152,153,154,155,156,157,158,159,160,161,162,163,164,165,166,167]. …”
Section: Promising Applications Of Superhydrophobic Fabricsmentioning
confidence: 99%
“…The treatment has increased activation of the fabric surface and increased TiO 2 absorption for more efficient and durable self-cleaning [149]. In addition to self-cleaning ability, Rana et al reported that the Ag@ZnO nanostructures functionalized flexible cotton fabrics exhibited efficient visible-light photocatalysis and antibacterial activity [150] (Figure 14b).…”
Section: Promising Applications Of Superhydrophobic Fabricsmentioning
confidence: 99%
See 1 more Smart Citation